Has high-resolution manometry changed the approach to esophageal motility disorders? - Bansal, Ajay (2010)
PURPOSE OF REVIEW: High-resolution manometry (HRM) coupled with high-resolution esophageal topography plots (HREPT) has dramatically changed the paradigm of manometric studies. The purpose of the current review is to discuss the salient advantages of HRM that are likely to change the clinical practice of manometry. RECENT FINDINGS: Recent studies evaluating HRM suggest a significant improvement in the sensitivity for the diagnosis of achalasia when compared with conventional manometry. By reproducibly subtyping achalasia into classic achalasia, achalasia with pressurization, or spastic achalasia with differential responses to treatment, HRM has potential to predict clinical outcomes. Preliminary observations with HRM suggest that much of what was labeled distal esophageal spasm is in fact achalasia with esophageal compression and pseudorelaxation, or spastic achalasia. HRM is capable of selectively analyzing discrete esophagogastric junction contributors (lower esophageal sphincter and crural diaphragm) during deglutitive relaxation to clearly identify the site of abnormally high outflow resistance. HRM has improved the recognition of a clinically heterogeneous entity called functional obstruction with potential for directed therapy. SUMMARY: Improved, accurate and reproducible recognition of manometric diagnoses by HRM will allow the clinician to confidently diagnose esophageal disorders such as achalasia, direct therapy and predict outcomes.